TheoArtistry, and a Contemporary Perspective on Composing Sacred Choral Music - George Corbett (Religions, 2017)
This article presents the methodology and research underpinning the TheoArtistry Composers’ Scheme, a project based in ITIA (the Institute for Theology, Imagination and the Arts), School of Divinity, University of St Andrews (2016–2017). I analyse Sir James MacMillan’s theology of music, outline some practical and theoretical issues that arose in setting up theologian-composer partnerships, and reflect critically on the six new works of sacred choral music that emerged (these are printed as supplementary materials). The article assesses the implications of such collaboration for future work at the interface between theology and music, and between theology and the arts more generally.